Papers of Mike Ladd - Ladd, Mike, 1959- (1992)
The collection comprises two boxes of files relating to the ABC Radio National Program Poetica, which ran for 18 years and reached weekly audience of 90,000 listeners. Poetica was first broadcasted in February 1997 and continued until February 2015. Mike Ladd has collected this material in the course of the 18 years spent as the program editor and coordinator of the Poetica weekly program broadcasted on ABC Radio National. Program covered Australian and international poetry. The collection contains complete list of programs and subjects, program briefs, publicity flyers, press clippings and correspondence with Australian authors and publishers, and letters from listeners.
Manuscript reference number: MS 10669.
Mike Ladd is an Australian, and was born in 1959 in Berkeley, California and moved to Australia when he was one. Ladd is a poet and a radio presenter, and was the founding producer of Poetica, a weekly program of poetry broadcasted on ABC Radio National from 1997 to 2015.
Keywords: Ladd, Mike, -- 1959- -- Archives; Australian Broadcasting Commission; Broadcasters -- Australia -- Archives; Radio producers and directors -- Australia -- Archives; Radio programs -- Australia; Poetry -- Appreciation -- Australia